Gastric Schwannoma: A Rare but Important Differential Diagnosis of a Gastric Submucosal Mass - William Yoon; Kari Paulson; Paul Mazzara; Sweety Nagori; Mohammed Barawi; Richard Berri (Case Reports in Surgery)
Schwannomas are generally slow growing asymptomatic neoplasms that rarely occur in the GI tract. However, if found, the most common site is the stomach. Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, and 60–70% of them occur in the stomach. Owing to their typical presentation as submucosal neoplasms, gastric schwannomas and GISTs appear grossly similar. Accordingly, the differential diagnosis for a gastric submucosal mass should include gastric schwannomas. Furthermore, GI schwannomas are benign neoplasms with excellent prognosis after surgical resection, whereas 10–30% of GISTs have malignant behavior. Hence, it is important to distinguish gastric schwannomas from GISTs to make an accurate diagnosis to optimally guide treatment options. Nevertheless, owing to the paucity of gastric schwannomas, the index of suspicion for this diagnosis is low. We report a rare case of gastric schwannoma in 53-year-old woman who underwent laparoscopic partial gastrectomy under the suspicion of a GIST preoperatively but confirmed to have a gastric schwannoma postoperatively. This case underscores the importance of including gastric schwannomas in the differential diagnosis when preoperative imaging studies reveal a submucosal, exophytic gastric mass. For a gastric schwannoma, complete margin negative surgical resection is the curative treatment of choice.